2013
DOI: 10.1124/jpet.113.203927
|View full text |Cite
|
Sign up to set email alerts
|

Selective Kinin Receptor Agonists as Cardioprotective Agents in Myocardial Ischemia and Diabetes

Abstract: Cardiac ischemia is a leading cause of death, especially in diabetic patients. The diabetic ischemic heart is resistant experimentally to established cardioprotective treatments. New pharmacological approaches to cardiac protection are warranted. The kallikrein-kinin system is involved in myocardial protection in ischemia. Respective roles of B1 (B1R) and B2 (B2R) receptors remain controversial. We tested whether pharmacological activation of kinin receptors may have therapeutic effect in cardiac ischemia-repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 54 publications
4
43
0
1
Order By: Relevance
“…This is in contrast with cardiac ischemia where B1R, but not B2R, activation reduces ischemia-reperfusion damage in diabetic mice (Potier et al, 2013). These findings indicate that, although diabetes suppresses B2R signaling in the heart, it does not alter B2R function in proangiogenic cells.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This is in contrast with cardiac ischemia where B1R, but not B2R, activation reduces ischemia-reperfusion damage in diabetic mice (Potier et al, 2013). These findings indicate that, although diabetes suppresses B2R signaling in the heart, it does not alter B2R function in proangiogenic cells.…”
Section: Discussionmentioning
confidence: 72%
“…As the B2R agonist dose dependently decreases blood pressure during acute administration in mice (Potier et al, 2013), we assessed the blood pressure effect of chronic B2R agonist treatment in dedicated groups of mice. In brief, four groups of 10-week-old male C57BL/6J mice, diabetic or not (n 5 10/group; Charles River Laboratories), were treated with 720 nmol/kg×day 21 or vehicle (saline) for 5 weeks via Alzet minipump.…”
Section: Blood Pressure Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…This was associated with a failure of these anesthetic agents to activate Akt, ERK1/2, GSK-3b (Tai et al, 2012), and STAT3 (Drenger et al, 2011). An interesting study by Potier et al (2013) suggested that there may be differential effects in the response to cardioprotection using different bradykinin receptor agonists in the presence of diabetes. It was shown that ischemic postconditioning, the angiotensin-converting enzyme (ACE) inhibitor ramiprilat or a bradykinin B 2 receptor agonist, all reduced infarct size and activated Akt, ERK1/2, and GSK-3b in the nondiabetic heart but failed to do so in the diabetic heart (Potier et al, 2013).…”
Section: Diabetesmentioning
confidence: 99%
“…An interesting study by Potier et al (2013) suggested that there may be differential effects in the response to cardioprotection using different bradykinin receptor agonists in the presence of diabetes. It was shown that ischemic postconditioning, the angiotensin-converting enzyme (ACE) inhibitor ramiprilat or a bradykinin B 2 receptor agonist, all reduced infarct size and activated Akt, ERK1/2, and GSK-3b in the nondiabetic heart but failed to do so in the diabetic heart (Potier et al, 2013). In contrast, the diabetic heart, but not the nondiabetic heart, was found to be amenable to pharmacologic postconditioning using a bradykinin B 1 receptor agonist (Potier et al, 2013).…”
Section: Diabetesmentioning
confidence: 99%